PENGARUH HUMAN CAPITAL TERHADAP KINERJA AUDITOR (STUDI EMPIRIS PADA KANTOR AKUNTAN PUBLIK DI JAKARTA) - Yvonne Agustine Sudibyo (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2014)
The purpose of this research were to analyze individual capability, individual motivation, leadership factor, organizational climate will influence the public accountants’ performances in CPA Firm at DKI Jakarta. Data were collected by distributing questionnaires to external auditors working at CPA Firm and only 127 respondents returned and used in this research. The result of this research showed that individual capability, individual motivation and workgroup effectiveness have no influence on auditor performane, but significant influence from leadership and organizational climate. Future research should consider the experience of auditor in demographic respondent and used sample CPA from other big cities.